Assessment of Insulin Resistance in Polycystic Ovary Syndrome Patients (Journal of Dhaka National Medical College & Hospital, 2024)
Background: Polycystic Ovarian Syndrome (PCOS) is a common Gynecological condition marked by anovulation and hyperandrogenism, affecting 7-8% of reproductive-age women. It's a leading cause of treatable infertility. Many PCOS patients also show metabolic syndrome signs like insulin resistance, obesity, and dyslipidemia.Objective: To assess the insulin resistance in polycystic ovary syndrome patients.Methods: This was a case-control study that was conducted in the Department of Obstetrics & Gynecology, Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2015 to December 2016. This study included 51 women aged 20-35 with polycystic ovary syndrome (PCOS). Data analysis was performed with MS Office tools and SPSS Version 23.0.Results: Among the total participants, the mean s. testosterone was 1.8±0.9 ng/ml and D2 s. LH was 12.7±6.7 mIU/mL; the difference was statistically significant (p3.2 had higher testosterone, LH, and insulin levels compared to those with HOMA-IR